KINERJA KARYAWAN BANK X: PELATIHAN, PENGAWASAN, DISIPLIN KERJA - FEBRIYANTI, NADYA; NURWANTI, NURWANTI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2023)
This study aims to analyze and determine the effect of training, supervision, and work discipline on employee performance at Bank X. The population used in this study are non-managerial employees at Bank X has 85 employees. The sampling technique used was saturated sampling with a sample of 85 non-managerial employees. Data collection techniques through distributing questionnaires using a Likert scale. The data were then analyzed using a statistical program. Based on the results of hypothesis testing data analysis in this study, it shows that supervision and work discipline affect employee performance. While training does not affect employee performance.